2016
DOI: 10.1007/s12311-016-0840-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Cerebellum by Noninvasive Neurostimulation: a Review

Abstract: Transcranial magnetic and electric stimulation of the brain are novel and highly promising techniques currently employed in both research and clinical practice. Improving or rehabilitating brain functions by modulating excitability with these noninvasive tools is an exciting new area in neuroscience. Since the cerebellum is closely connected with the cerebral regions subserving motor, associative, and affective functions, the cerebello-thalamo-cortical pathways are an interesting target for these new technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 217 publications
2
74
0
1
Order By: Relevance
“…The links between learning, compensation/decompensation, and cerebellar reserve require specific studies. This is a critical point at a time when techniques such as transcranial direct current stimulation (tDCS) or repetitive transcranial magnetic stimulation (rTMS) are increasingly used to promote recovery [35]. One example of the importance of the delineation of cerebellar reserve comes from the observation that animals undergoing both cortical hemispherectomy and contralateral cerebellar resection cannot relearn motor tasks [34].…”
Section: The Compensation Following Transection Of Cerebellar Pedunclesmentioning
confidence: 99%
“…The links between learning, compensation/decompensation, and cerebellar reserve require specific studies. This is a critical point at a time when techniques such as transcranial direct current stimulation (tDCS) or repetitive transcranial magnetic stimulation (rTMS) are increasingly used to promote recovery [35]. One example of the importance of the delineation of cerebellar reserve comes from the observation that animals undergoing both cortical hemispherectomy and contralateral cerebellar resection cannot relearn motor tasks [34].…”
Section: The Compensation Following Transection Of Cerebellar Pedunclesmentioning
confidence: 99%
“…Furthermore, the NIBS to the cerebellum modulates cerebellar excitability [98,[129][130][131], motor function [132,133], and motor learning [32,[134][135][136][137][138] in healthy population. In patients with cerebellar ataxia, some previous studies reported about the effect of tDCS to the cerebellum on motor function [131,[139][140][141]. A double-blind, randomized and sham-controlled study revealed that cerebellar tDCS improved SARA, ICARS, nine-hole peg test, and gait speed [141].…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%
“…Due to its numerous connections with the motor and associative cortical regions, its high density of neurons (in particular in the cerebellar cortex), its electrical properties, and its position immediately below the skull, the cerebellum is now considered as a real target to modulate distant cortical regions [9,10].…”
Section: Introductionmentioning
confidence: 99%